Development of Tourism Promotion through New Media by the Village Government in North Minahasa Regency - Elfie Mingkid; Edmon R. Kalesaran; Sintje A. Rondonuwu; Evie A. Suwu (Journal La Bisecoman, 2024)
Regency North Minahasa is one of them districts that have potency very tourism big in support development Indonesian tourism. Tourist area likupang is one of incoming area in 5 (five) destinations super priority tourism launched by the Ministry of Tourism and Creative Economy (Kemenparekraf), apart from Borobudur, Lake Toba, Mandalika and Labuan Bajo. A number of potency tourist interesting likupang such as beach Pulisan, Paal beach and ecotourism Bahoi, government central and regional naturally very enthusiastic For developing potency tourist This is also supported by the community local. Government besides from center through ministry, North Sulawesi province and district North Minahasa, of course inside it It also needs to be supported by the government at the lower level, namely government village, which is very close by with potency tourist the. Objective from study This is For know How development promotion tourist through new media, internet platforms, whether Can utilized optimally deep support promotion tourism by the government village around area tourism in Linkoping that, will studied in a way deep through study this, with approach in a way qualitative descriptive. Problem Not yet optimally use of new media by the government, as well ability management communication and information by the government village become base problem in study This. Study this too of course in accordance with plan strategic study unsrat 2021 – 2025, with focus superior field tourist sustainable and appropriate with topic research related with economy and resources man supporter tourist.